2021
DOI: 10.3892/mmr.2021.11859
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Notch1 on neural tube defects and neural stem cell differentiation induced by all‑trans retinoic acid

Abstract: Neural tube defects (NTDs) are the most serious and common birth defects in the clinical setting. The Notch signaling pathway has been implicated in different processes of the embryonic neural stem cells (NSCs) during neural tube development. The aim of the present study was to investigate the expression pattern and function of Notch1 (N1) in all-trans retinoic acid (atRA)-induced NTDs and NSC differentiation. A mouse model of brain abnormality was established by administering 28 mg/kg atRA, and then brain dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Worldwide, 1 in every 1000 pregnancies has a NTD and they cause enormous clinical, economic, and societal costs (Fimia et al 2007 ; Zhang et al 2016 ). Since China implemented a nationwide folic acid supplementation program in 2009, the prevalence of NTDs has dropped from 7.8% to 3.1% in five years (Chen et al 2021a ). Although many studies have confirmed that strengthening folic acid intake during perinatal pregnancy can reduce the incidence and recurrence rate of NTDs, not all types of NTDs can be prevented, so in-depth research into the causes of the disease is important to advance its diagnosis, treatment and research (Cao et al 2024 ).…”
Section: Discussionmentioning
confidence: 99%
“…Worldwide, 1 in every 1000 pregnancies has a NTD and they cause enormous clinical, economic, and societal costs (Fimia et al 2007 ; Zhang et al 2016 ). Since China implemented a nationwide folic acid supplementation program in 2009, the prevalence of NTDs has dropped from 7.8% to 3.1% in five years (Chen et al 2021a ). Although many studies have confirmed that strengthening folic acid intake during perinatal pregnancy can reduce the incidence and recurrence rate of NTDs, not all types of NTDs can be prevented, so in-depth research into the causes of the disease is important to advance its diagnosis, treatment and research (Cao et al 2024 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another study by Zhang et al, 2017 also shows an increase in p-Akt in rat primary cortical neurons post-valproate treatment (Table 2). All of the above pathways are also reported to play an important role in neural tube closure defects (Rolo et al, 2018; Bekri et al, 2019; Han et al, 2020; Chen et al, 2021; Li et al, 2021; Tian et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Experimental studies on mouse models have shown that overexpression of retinoic acid leads to neural tube defects ( 236 , 237 ). A recent study found that treatment of neural crest cells (NSCs) with all-trans-retinoic acid culminates in neural tube deformities ( 238 ). Notch signaling pathway: The notch signaling pathway regulates the proliferation and differentiation of NSCs (neural crest cells) during embryonic development.…”
Section: Signaling Pathways—neural Tube Defectsmentioning
confidence: 99%
“…Previous Studies observed that mutation in the genes Hes1, Hes3, and RBP-Jκ of the Notch signaling pathway contributes to neural tube anomalies ( 121 , 149 ). A recent study observed that abnormal expression of N1 (Notch1) enforces the occurrence of neural tube deformities ( 238 ). A study conducted on embryonic stem cells showed that the double mutant embryo of CSL (CBF-1/Suppressor of hairless/Lag-1) displays the phenotypes of neural tube defects ( 241 ).…”
Section: Signaling Pathways—neural Tube Defectsmentioning
confidence: 99%
See 1 more Smart Citation